Celebrity Endorsement and Content Instamarketing of Purchase Intention Beauty Products - Meilisya Nurfazzar Abdurohim; Kokom Komariah; R Deni Muhammad Danial (Almana : Jurnal Manajemen dan Bisnis, 2021)
Instagram is a social media that is widely used by people to find information. Pixy Cosmetics company uses Instagram and using celebrity endorsement as a spokesperson to create purchase intention. The research was aimed at determining the effect of celebrity endorsement and content marketing toward purchase intention on Pixy Cosmetics products. The data analysis technique used in this study is multiple regression analysis techniques including multiple correlation coefficient tests and hypothesis testing partial (t-test). The results of the study used multiple correlations with an R Square value of 0.563 or 56.3%, this indicates that celebrity endorsement and content marketing can explain the purchase intention of 56.3% and 43.7% explained by other variables. While the R-value is 0.75 and the interval coefficient is between 0.60-0. 799 which shows the level of a strong relationship between the celebrity endorsement variable and content marketing on purchase intention. The results obtained from the partial test (t-test) of the celebrity support variable obtained tcount value of 5.218 ≥ ttable 1.65, meaning that the celebrity endorsement variable can have a positive effect on purchase intention. And for the content marketing variable, tcount value of 6.668 ≥ ttable 1.65, meaning that the content marketing variable can have a positive effect on purchase intention.